Analysis of the Impact of Human Resource Quality on Economic Performance: A Comparative Study of Indonesia in the ASEAN Context Based on World Bank Data - Venna Annisa Malinda; Ma'rifatul Hikmah (Journal of Innovative and Creativity, 2026)
Improving human resource quality is a strategic issue in accelerating economic growth, especially in the ASEAN region, which is undergoing significant economic transformation. This study aims to analyse the effect of human resource quality on Indonesia's economic performance in a regional comparative context with other ASEAN countries. The research method uses a quantitative approach through panel data regression analysis from the World Bank for the period 2015-2023, supplemented with diagnostic tests and robustness checks to ensure the validity of the results. The findings reveal an interesting contradiction where Indonesia excels in higher education participation and MSME gender inclusion, but has not been able to transform this into economic competitive advantage. The regression model shows limited explanatory power with an R-squared of only 1.83%, indicating the existence of other determining factors beyond the human resource quality variable. The study concludes that there is a need for a more integrated policy approach between human capital development and structural reform in the real sector. The limitations of the study lie in its failure to include institutional variables and governance quality, which are believed to strongly influence the relationship between human capital quality and economic performance. The next research agenda is recommended to develop a more comprehensive model by including variables of technological innovation, bureaucratic efficiency, and investment in research and development in order to gain a more holistic understanding of the determinants of economic growth in the ASEAN region.